Anak Dayak Bahasa Banjar: Dominasi Bahasa Pendatang pada Masyarakat Dayak Ngaju di Desa Pulau Telo - Handayani, Putri; Hakim, Arif Rahman (Huma: Jurnal Sosiologi, 2025)
The extinction of regional languages ​​as a form of customs and identity of a region caused by the arrival of more dominant immigrant languages, is now a problem that occurs in Indonesia as a culturally rich country, one of the regional languages ​​which is currently experiencing a crisis of young generation speakers in its own region is the Dayak Ngaju language as the traditional language of the people of Central Kalimantan. This research aims to examine the process of Banjar language dominance among Dayak Ngaju children in Pulau Telo village, Kapuas Regency, Central Kalimantan Province. The approach used is a qualitative approach with a case study type of research. Data collection was carried out through unstructured observation, in-depth interviews and documentation. Data analysis uses the model from Miles and Huberman. The results of the research found that the majority of children in Pulau Telo Village communicate more using Banjar language compared to Dayak language in every interaction in their activities. The process of dominating the Banjar language can occur because it goes through several processes, starting with the dominance of the Banjar language which first occurred in Kuala Kapuas City as the Regency Capital until it had an impact on the people of Pulau Telo Village, especially on children who were in the middle phase. childhood is a more empirical attitude towards the outside world. This domination process is then carried out by the role of social agents in the children's environment, namely parents, teachers, peers, mass media, socialization agents in the market. These five social agents have a big influence in forming the habits of Telo Island village children in implementing the culture of speaking, Therefore, it is very important to teach children as the younger generation to continue using Dayak language only as a form of preserving the regional language.